Assistance of pregnant women with HIV care in testing and counseling centers in the professional perspective - Fabiani Weiss Pereira; Michele Bulhosa de Souza; Neila Santini de Souza; Eliane Tatsch Neves; Andressa da Silveira (Universidade Federal de Santa Maria, 2012)
Objective: this is a qualitative research that aimed to know the work developed by health professional of testing and counseling centers for AIDS (TCC) in the assistance to pregnant women with Human Immunodeficiency Virus HIV/AIDS. Method: data were collected by semi structured interviews with 11 health professional of CTC in the city of the southern Brazil in May 2010. Data were submitted to content thematic analyses. Results: it was organized in two categories: the difficulties of adhesion to treatment by pregnant women in the professional perspective, and the strategies of adhesion to treatment as challenges to professionals. Conclusion: in conclusion the training of professional is necessary in order to provide assistance that priory the receptiveness. We recommend that the entire professional of TCC offered a following that consider the necessities and singularities of each woman